Martinus Nijhoff, de literaire vertaler - Varga, Orsolya (Acta Neerlandica, 2024)
Martinus Nijhoff (The Hague 1894–1953), the Dutch poet, playwright, literary translator and essayist is today considered the greatest modern Dutch poet and is probably the best known. Apart from his original work, he is the best-known literary translator of his time, and his approach to language is most vividly expressed in his translations. Translation is not just a sideline activity: he sees it as a rebirth of the poem. In this paper, I will attempt to outline his approach to translation, based on both his translation critiques and his own translations.